(untitled) (American Journal of Business Management, Economics and Banking, 2025)
This article examines the interaction of ecology and economy today. Various approaches to the possibilities of solving global environmental problems through the active introduction of modern financial instruments are studied. The role of "green bonds" in the global financial market and the features of investing in the development of renewable energy sources are also studied. In order to reduce environmental risks in the country’s economy, the work carried out on the transition to a green economy is analyzed, and proposals and recommendations are made in this regard.